IMPLEMENTASI PENDEKATAN STEAM TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIVITAS SISWA SEKOLAH DASAR - Eko Ferianto, Anggun; Suprapto, Nadi; Suryanti, Suryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low ability of students to think critically and creatively in elementary education negatively impacts the learning process, resulting in suboptimal outcomes. Education plays an important role for every student, especially primary school education, in developing critical thinking and creativity skills. In the era of Society 5.0, which is full of competition, students need to be aware of the rapidly advancing technological developments. Therefore, a technology-focused learning approach is needed. The STEAM approach is a learning method that can encourage students to enhance their information processing and communication skills for critical thinking, while also boosting their creativity in connecting various facts and phenomena encountered during the learning process. This research aims to analyze the STEAM (Science, Technology, Engineering, Art, and Mathematics) learning approach in education, so that students can enhance their critical thinking and creativity skills. The research method used in this study is a literature review, by analyzing theoretical references from various Sinta journals that align with the implementation of the STEAM approach. This STEAM approach can improve students' critical thinking and creativity skills, enabling them to better develop their competencies.